Asymmetry of Hemispheric Network Topology Reveals Dissociable Processes between Functional and Structural Brain Connectome in Community-Living Elders - Sun, Yu; Li, Junhua; Suckling, John; Feng, Lei (Frontiers in Aging Neuroscience, 2017)
Human brain is structurally and functionally asymmetrical and the asymmetries of brain phenotypes have been shown to change in normal aging. Recent advances in graph theoretical analysis have showed topological lateralization between hemispheric networks in the human brain throughout the lifespan. Nevertheless, apparent discrepancies of hemispheric asymmetry were reported between the structural and functional brain networks, indicating the potentially complex asymmetry pattern between structural and functional networks in aging population. In this study, using multimodal neuroimaging, we investigated the characteristics of hemispheric network topology in seventy-six (male/female = 15/61) community-dwelling older adults. Multimodal neuroimaging data, including resting-state fMRI and structural diffusion tensor imaging were recorded from 78 older adults. Hemispheric functional and structural brain networks were obtained for each participant. Graph theoretical approaches were then employed to estimate the hemispheric topological properties. We found that the optimal small-world properties were preserved in both structural and functional hemispheric networks in older adults. Moreover, a leftward asymmetry in both global and local levels were observed in structural brain networks in comparison with a symmetric pattern in functional brain network, suggesting a dissociable process of hemispheric asymmetry between structural and functional connectome in healthy older adults. Finally, the scores of hemispheric asymmetry in both structural and functional networks were associated with behavioral performance in various cognitive domains. Taken together, these findings provided new insights into the lateralized nature of multimodal brain connectivity, highlighted the potentially complex relationship between structural and functional brain network alterations, and augmented our understanding of asymmetric structural and functional specializations in normal aging.